Tác dụng trừ sâu hại rau của chế phẩm momosertatin tách từ hạt gấc - Trân Châu, Phạm Thị; Hà, Phan Thi; Toàn, Mai Ngoc; Thái, Trịnh Hồng; Tấn, Trần Quang; Việt, Hoàng Thị; Toàn, Nguyễn Đậu; Hạnh, Phạm Thị (VNU Journal of Science: Natural Sciences and Technology; Vol 16 No 1, 2000)
Abstract